2022
DOI: 10.1038/s41380-022-01775-5
|View full text |Cite
|
Sign up to set email alerts
|

Working memory and reaction time variability mediate the relationship between polygenic risk and ADHD traits in a general population sample

Abstract: Endophenotypes are heritable and quantifiable traits indexing genetic liability for a disorder. Here, we examined three potential endophenotypes, working memory function, response inhibition, and reaction time variability, for attention-deficit hyperactivity disorder (ADHD) measured as a dimensional latent trait in a large general population sample derived from the Adolescent Brain Cognitive DevelopmentSM Study. The genetic risk for ADHD was estimated using polygenic risk scores (PRS) whereas ADHD traits were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 98 publications
1
3
0
Order By: Relevance
“…These results were generally consistent with crosssectional work, demonstrating that working memory difficulties predict organizational problems even when controlling for ADHD symptoms (Kofler, Sarver, Harmon, et al, 2018). Collectively, these findings contribute to the quickly growing evidence base linking working memory with ADHD behavioral symptoms (e.g., Kofler et al, 2011;Raiker et al, 2012;Rapport et al, 2009), functional impairments (e.g., Kofler et al, 2011;Singh et al, 2022), and genetic risk for ADHD (Moses et al, 2022).…”
Section: Discussionsupporting
confidence: 78%
“…These results were generally consistent with crosssectional work, demonstrating that working memory difficulties predict organizational problems even when controlling for ADHD symptoms (Kofler, Sarver, Harmon, et al, 2018). Collectively, these findings contribute to the quickly growing evidence base linking working memory with ADHD behavioral symptoms (e.g., Kofler et al, 2011;Raiker et al, 2012;Rapport et al, 2009), functional impairments (e.g., Kofler et al, 2011;Singh et al, 2022), and genetic risk for ADHD (Moses et al, 2022).…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, our recent study also revealed that individuals with higher proactive control, characterized by lower SD-RT, experienced greater benefits from negative cues (Chidharom & Carlisle, under review). The current results suggest that individuals with lower SD-RT demonstrate higher working memory capacity (Buzy et al, 2009 ; Kofler et al, 2014 ; Moses et al, 2022 ), enabling them to effectively engage proactive control to suppress cued distractors. Overall, our findings highlight the critical role of VWM capacities in efficiently utilizing negative cues and suggest that individuals with higher working memory capacity demonstrate enhanced engagement of proactive control to suppress distractors.…”
Section: Discussionmentioning
confidence: 69%
“…In light of these ndings, the socio-economic environment of a family could impact a child's cognitive variability. Beyond these familial environments, hereditary factors might further (at least in part) explain variability (Moses et al, 2022). For this reason, a subset of parents will perform the same cognitive tasks as their children, allowing us to quantify the within-family similarities above and beyond other factors.…”
Section: Environmental Factorsmentioning
confidence: 99%